The Women’s Health Initiative: the Food Environment, Neighborhood Socioeconomic Status, Body Mass Index and Blood Pressure - Dubowitz, T. (2011)
Using data (n=60,775 women) from the Women’s Health Initiative Clinical Trial (WHI CT)— a national study of postmenopausal women aged 50 to 79 years — we analyzed cross-sectional associations between the availability of different types of food outlets in the 1.5 miles surrounding a woman’s residence, census tract neighborhood socioeconomic status (NSES), body mass index (BMI) and blood pressure (BP). We simultaneously modeled NSES and food outlets using linear and logistic regression models, adjusting for multiple socio-demographic factors, population density and random effects at the tract and metropolitan statistical area (MSA) level. We found significant associations between NSES, availability of food outlets and individual-level measurements of BMI and BP. As grocery store/supermarket availability increased from the 10th to the 90th percentile of its distribution, controlling for confounders, BMI was lower by 0.30 kg/m2. Conversely, as fast-food outlet availability increased from the 10th to the 90th percentile, BMI was higher by 0.28 kg/m2. When NSES increased from the 10th to the 90th percentile of its distribution, BMI was lower by 1.26 kg/m2. As NSES increased from the 10th to the 90th percentile, systolic and diastolic BP were lower by 1.11 mm and 0.40 mm Hg, respectively. As grocery store/supermarket outlet availability increased from the 10th and 90th percentiles diastolic BP was lower by 0.31 mm Hg. In this national sample of post-menopausal women, we found important independent associations between the food and socioeconomic environments and BMI and BP. These findings suggest that changes in the neighborhood environment may contribute to efforts to control obesity and hypertension.